2019
DOI: 10.5483/bmbrep.2019.52.7.042
|View full text |Cite
|
Sign up to set email alerts
|

ATAD2 expression increases [18F]Fluorodeoxyglucose uptake value in lung adenocarcinoma via AKT-GLUT1/HK2 pathway

Abstract: [18F]Fluorodeoxyglucose (FDG) PET/CT imaging has been widely used in the diagnosis of malignant tumors. ATPase family AAA domain-containing protein 2 (ATAD2) plays important roles in tumor growth, invasion and metastasis. However, the relationship between [18F]FDG accumulation and ATAD2 expression remains largely unknown. This study aimed to investigate the correlation between ATAD2 expression and [18F]FDG uptake in lung adenocarcinoma (LUAD), and elucidate its underlying molecular mechanisms. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…We further assessed the role of SKA3 in EMT processes [22][23][24][25] but no associations were observed. Upon further analysis, we found that AKT activation strongly correlated with SKA3 expression, and that the expression of MMP following SKA3 silencing decreased in a manner that could be rescued by exogenous AKT overexpression, suggestive that SKA3 influences MMP-2, -7 and -9 to promote of LUAD occurrence and development [26][27][28][29][30][31][32]. These data further suggested that the selective modulation of SKA3 during EGFR-PI3K-AKT signaling in LUADs leads to EGF modulation, with no effects on HGF-signaling.…”
Section: Discussionmentioning
confidence: 94%
“…We further assessed the role of SKA3 in EMT processes [22][23][24][25] but no associations were observed. Upon further analysis, we found that AKT activation strongly correlated with SKA3 expression, and that the expression of MMP following SKA3 silencing decreased in a manner that could be rescued by exogenous AKT overexpression, suggestive that SKA3 influences MMP-2, -7 and -9 to promote of LUAD occurrence and development [26][27][28][29][30][31][32]. These data further suggested that the selective modulation of SKA3 during EGFR-PI3K-AKT signaling in LUADs leads to EGF modulation, with no effects on HGF-signaling.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, ATAD2 promotes tumor progression as a coactivator of the hormone-induced nuclear receptors ERα and androgen receptor (AR), E2Fs and c-Myc 38 . In lung adenocarcinoma and gastric cancer, ATAD2 could promote cell proliferation via the phosphatidylinositol 3 kinase (PI3K) / AKT pathway and the retinoblastoma tumor suppressor protein (Rb)-E2F-cMyc signaling 39 , 40 . While in lung adenocarcinoma, the knockdown of ATAD2 affects glucose metabolism in cancer cells by regulating [18F] FDG uptake and lactate production through the AKT-GLUT1 / HK2 pathway 39 .…”
Section: Atad2 In Cancermentioning
confidence: 99%
“…In lung adenocarcinoma and gastric cancer, ATAD2 could promote cell proliferation via the phosphatidylinositol 3 kinase (PI3K) / AKT pathway and the retinoblastoma tumor suppressor protein (Rb)-E2F-cMyc signaling 39 , 40 . While in lung adenocarcinoma, the knockdown of ATAD2 affects glucose metabolism in cancer cells by regulating [18F] FDG uptake and lactate production through the AKT-GLUT1 / HK2 pathway 39 . In addition, silencing ATAD2 also inhibits the growth and colony formation ability of esophageal squamous cell carcinoma (ESCC) cells, and significantly inhibits ESCC tumor growth in vitro 41 .…”
Section: Atad2 In Cancermentioning
confidence: 99%
“…The study further pointed out that this was caused by ATAD2 promoting LUAD glucose metabolism via the AKT-GLUT1/HK2 pathway. In addition, ATAD2 also promotes the proliferation, tumorigenicity, and migration of lung cancer cells utilizing the PI3K/AKT pathway [ 47 ]. ATAD2 knockdown inhibited the migration, invasion, stem cell-like properties, and mitochondrial reactive oxygen species (mtROS) production of lung cancer cells.…”
Section: The Role Of Atad2 In Human Malignant Tumorsmentioning
confidence: 99%
“…The integrity of HIF-1α/ATAD2 triggered by CIH may determine the aggressiveness of lung cancer through the interaction of mtROS and stemness in lung cancer cells [ 48 ]. ATAD2 overexpression is closely associated with positive LUAD lymph node metastasis, poor tumor differentiation, advanced disease stage, and prognosis, and it is an individual marker of adverse prognosis after surgical resection of lung adenocarcinoma [ 5 , 47 , 126 , 127 ].…”
Section: The Role Of Atad2 In Human Malignant Tumorsmentioning
confidence: 99%